Cartilla de administración municipal - Ramírez, Germán A. (Editorial CESA, Colegio de Estudios Superiores de Administración, 2015)
This handbook was developed and designed by the Corporación Pensamiento Siglo XXI as a tool for elected officials and others interested in the management of municipal government.